The ice-core stable isotope records from small Arctic ice caps as proxis of climatic and evironmental changes ... - Vaikmäe, Rein; Martma, Tõnu; Isaksson, Elisabeth; Divine, Dmitry; Pohjola, Veijo; Meijer, Harro (TalTech Data Repository, 2022)
Stable water isotopic composition (δ18O and δD) of ice cores is commonly known as one of the most valuable paleo-climate proxies for temperature conditions of the precipitation formation in the past. The observed relationship between air temperature and isotopic content of the precipitation both geographical and temporal has been robustly confirmed experimentally and explained theoretically. Isotopic data extracted from deep ice cores from the polar ice sheets have contributed much information on climate variability both on inter-annual and ice ages time scales. However, most of the available ice core records from the northern hemisphere are from the cold dry firn zone in interior Greenland. https://meetingorganizer.copernicus.org/EGU2011/EGU2011-8934-1.pdf ...